PENGUKURAN TINGKAT KEPUASAN MAHASISWA DALAM PENGGUNAAN SISTEM INFORMASI AKADEMIK MENGGUNAKAN PIECES FRAMEWORK (Studi Kasus : STMIK Nusa Mandiri kampus Depok) - Wina Widiati (LPPM Universitas Bina Sarana Informatika, 2016)
The presence of information systems has given so much influence over a company, not just the organization but the effect extends to the business processes and transactions of the organization. But whether all information systems applied to the organization can be considered successful? Then how organizations can determine the success of applied information systems and how to create an information system to be successful. STMIK Nusa Mandiri has web-based academic information system is divided into two groups, namely the lecturers and students. In terms of student academic information system is needed because all academic information such as schedule of lectures, exams, guidance, and so on. Given that academic information system is used to meet the needs of user groups were students, to the need for an act of evaluation of the quality of the academic information systems. Reference used in relation to the analysis of information systems audit with the results of the performance of a system both quantitatively and qualitatively. In this study, we will use the analysis model PIECES Framework. PIECES Framework is an evaluation model that scales information system used to classify a problem, opportunities, and the directives contained in the scope definition analysis and system design. The results of this study showed the average value of user satisfaction from the results of calculations which show that students already feel SATISFIED in the use of academic information systems STMIK Nusa Mandiri Depok campus. Keywords : Satisfaction, PIECES Framework, Academic Informations System.